Ocean Acidification From Below in the Tropical Pacific. Issue 8 (20th August 2020) - Ishii, Masao; Rodgers, Keith B.; Inoue, Hisayuki Y.; Toyama, Katsuya; Sasano, Daisuke; Kosugi, Naohiro; Ono, Hisashi; Enyo, Kazutaka; Nakano, Toshiya; Iudicone, Daniele; Blanke, Bruno; Aumont, Olivier; et al.
Abstract: Identifying ocean acidification and its controlling mechanisms is an important priority within the broader question of understanding how sustained anthropogenic CO2 emissions are harming the health of the ocean. Through extensive analysis of observational data products for ocean inorganic carbon, here we quantify the rate at which acidification is proceeding in the western tropical Pacific Warm Pool, revealing −0.0013 ± 0.0001 year −1 for pH and −0.0083 ± 0.0007 year −1 for the saturation index of aragonite for the years 1985–2016. However, the mean rate of total dissolved inorganic carbon increase (+0.81 ± 0.06 μmol · kg −1 · year −1 ) sustaining acidification was 20% slower than what would be expected if it were simply controlled by the rate of atmospheric CO2 increase and transmitted through local air‐sea CO2 equilibration. Joint Lagrangian and Eulerian model diagnostics indicate that the acidification of the Warm Pool occurs primarily through the anthropogenic CO2 that invades the ocean in the extra‐tropics is transported to the tropics through the thermocline shallow overturning circulation and then re‐emerges into surface waters within the tropics through the Equatorial Undercurrent from below. An interior residence time of several years to decades, acting in conjunction with the accelerating CO2 growth in the atmosphere, can be expected to contribute to modulating the rate of Warm Pool acidification. Key Points: Progress of ocean acidification in the western tropical Pacific Warm Pool was identified using the data of oceanic CO2 measurements The rate of oceanic CO2 increase here was 20% lower than that expected from the growth rate of the mixing ratio of CO2 in the atmosphere Intergyre exchange of anthropogenic CO2 within the thermocline predominantly controls the rate of acidification in this region